Assessing the Anti-Epileptic and Anti-Nociceptive Potentials of Pepperomia pellucida in Pentylenetetrazol-Induced Epileptic Seizure in Mice - Enene, Esu Ukpai; Ajah, Obia Ukwula; Odey, Agnes I.; Ango, Alice Ashiya; Mobisson, Samuel (Kwaghe International Journal of Sciences and Technology, 2025)
Background: Epilepsy has become one of the major public health problems in the world is characterized by seizures resulting from abnormal electrical discharges in the brain. Hence, this study to assess the anti-epileptic and antinoceptive potentials of Pepperomia pellucida in pentylenetetrazol-induced epileptic mice model. Methods: Forty (40) Swiss male albino mice weighing 21 to 35kg were randomly assigned into four groups (A to D) ten mice each and treated as follows: Group A served as the control, Group B received pentylenetetrazol 35mg/kg intraperitoneally, Group C received pentylenetetrazol 35mg/kg intraperitoneally + peperomia pellucida 2mg/kg orally, and Group D received pentylenetetrazol 35mg/kg intraperitoneally + Diazepam 0.001ml/kg orally. Pentylenetetrazol 35mg/kg intraperitoneally was used to induce epilepsy and the animals were considered epileptic after few minutes with a jerky movement of the tail and limb progressing to the entire body. All animals had access to food and water ad libitum. After administration for 14 days, epilepsy was induced and then neurobehavioral studies for nociception was assessed using the formalin test. Results: pentylenetetrazol 35mg/kg had significant epileptic seizures scores as evidenced by increased duration of seizures, frequency of jerks, onset of tonic seizures and onset of seizures and also had significant edema of the animals’ paw. Peperomia pellucida significantly ameliorated the epileptic seizure and reduced the edema of the animals’ paw induced by the pentylenetetrazol. IBM SPSS statistical software version 20, was used to analyze the data p<0.001. Conclusions: It is based on these results, we draw the conclusion that Peperomia pellucida may possess anti-epileptic and anti-nociceptive properties that resulted in the significant reduction in the epileptic seizures and edema of the animals’ paw in the Peperomia pellucida treated group.